Channel theoretic approach to conditional reasoning - Cavedon, Lawrence (University of Edinburgh. College of Science and Engineering. School of Informatics., 1995)
Channel Theory is a recently developed mathematical model of information flow, based on ideas emanating from situation theory.Channel theory addreses a number of important properties of information flow, such as context-dependence, modularity of information, and the possibility of error.This thesis is concerned with the use of channel theory as a formal framework for various constructs relating to conditional sentences. In particular,the main concern is to obtain logics for reasoning about conditionals,generics and default properties within the channel theoretic framework.
A channel theoretic approach to conditional reasoning
Institute for Communicating and Collaborative Systems
Keywords: Channel Theory